Seismic control performance of a three‐story frame prototype equipped with semi‐active variable stiffness and damping structural joints. (23rd July 2021) - Wang, Qinyu; Senatore, Gennaro; Jansen, Kaspar; Habraken, Arjan; Teuffel, Patrick
Abstract: This paper presents numerical and experimental studies on semi‐active seismic response control of structures equipped with variable stiffness and damping structural joints. Such adaptive joints, which are comprised of a shape memory polymer (SMP) core reinforced by an SMP‐aramid composite skin, function as load‐transfer components as well as semi‐active control devices. The SMP core material can transition from a glassy to a rubbery state through thermal actuation resulting in a shift of the structural natural frequencies and a parallel increase of damping ratio, which enables a new semi‐active control strategy. Control performance has been evaluated on a three‐story frame equipped with 12 adaptive joints and subjected to seismic excitations. Full‐transient analysis has shown that when the joints are thermally actuated to the transition temperature (65°C), acceleration and base shear are reduced by up to 62% and 65%, respectively. Shake‐table tests have been carried out on a 1/10‐scale prototype, confirming that through thermal actuation of the adaptive joints the structural damping ratio increases from 2.6% to 11.3% and the first natural frequency shifts by up to 37%. As the structure becomes more flexible, an increase of displacements and interstory drift might occur. However, depending on the seismic excitation, top‐story acceleration and base shear are significantly reduced in the range 43%–50% and 35%–51%, respectively. These results confirm that semi‐active control through thermal actuation of variable stiffness and damping structural joints is effective to mitigate the structure response under seismic excitation.